Financial Profiles, Dividends and Stock Returns - Gunasekarage, Abeyratna (Universiti Utara Malaysia Press, 2015)
The aims of this paper are (a) to examine whether changes in dividend can be forecasted from past financial statement information and (b) to investigate whether such forecasts can be exploited to yield abnormal returns. A two-step approach is adopted. First, a logit model is developed to predict one year-ahead changes in dividends. Second, the buy-and-hold returns for a trading strategy based on the dividend forecasts are calculated. The logit model developed has some success in predicting future dividend changes. However, attempts to exploit these predictions proved unsuccessful; a strategy of buying (selling) shares where dividends were predicted to increase (decrease) would earn a negative abnormal return of -2.34% over 24 months. This is one of the first studies to forecast dividend changes for a sample of New Zealand companies using past financial statement data and to test if the market is semi-strong-form efficient with respect to these dividend predictions.